Positive Effects of Religion and Social Ties on the Health of Former NFL Athletes - Cupery, Tim (Journal of religion and health, 2023)
This study explores the relationship between religious service attendance, social ties, and health among former NFL players, a population with relatively high levels of religious attendance who endure physically demanding occupations. Research shows that frequent religious service attenders tend to have better health, partly because of social connections formed through religious involvement. We analyzed a sample of 1029 former NFL players. Consistent with previous research, bivariate and multivariate OLS regression models show that frequent religious attenders have statistically significantly better self-rated health. However, this relationship is moderated by social ties. Respondents who scored lower on the social ties index exhibited a stronger significant relationship between frequent religious attendance and health; those scoring higher on the social ties index exhibited no relationship between frequent attendance and health. Future research should examine how benefits of religious attendance vary depending upon strength of social relationships.